Excellent swiftlet - Ideris, Aini; Abdul Aziz, Saleha; Abu, Jalila (Universiti Putra Malaysia Press, 2015)
Universiti Putra Malaysia is given recognition as the National Center of Excellence (CoE) for Swiftlet Industry in 2011 under NKEA Agriculture (EPP#2). One of its important roles is to coordinate research studies on Malaysian edible-nest swiftlets and edible birdnests (EBNs) among higher learning institutions and research institutes in the country and to collaborate with industry players as partners in R&D.